Equation 1:

y=6x+2

Equation 2:

y=x+17

Equation 2 can also be written as:

x=y-17

Lets suppose this is equation 3

So:

Substituting equation 3 into equation 1;

y=6(y-17)+2

Expanding:

y=6y-102+2

Adding:

y=6y-100

Shifting 6y to the other side:

y-6y=-100

subtracting:

-5y=-100

dividing:

-y=-100/3

So:

-y=-33.33

Canceling the minus sign we get:

y=33.33

So the value of y is 33.33

To find the value of x lets substitute this value into equation 3. Hence:

x=y-17

x=33.33-17

Subtracting:

x=16.33

Hence the vale of x is 16.33

y=6x+2

Equation 2:

y=x+17

Equation 2 can also be written as:

x=y-17

Lets suppose this is equation 3

So:

Substituting equation 3 into equation 1;

y=6(y-17)+2

Expanding:

y=6y-102+2

Adding:

y=6y-100

Shifting 6y to the other side:

y-6y=-100

subtracting:

-5y=-100

dividing:

-y=-100/3

So:

-y=-33.33

Canceling the minus sign we get:

y=33.33

So the value of y is 33.33

To find the value of x lets substitute this value into equation 3. Hence:

x=y-17

x=33.33-17

Subtracting:

x=16.33

Hence the vale of x is 16.33